Expression Profile of Circulating MicroRNAs in Dogs With Cardiac Hypertrophy: A Pilot Study - Ro, Woong-Bin; Kang, Min-Hee; Song, Doo-Won; Lee, Sung-Hun; Park, Hee-Myung (Frontiers in Veterinary Science, 2021)
This study aimed to identify the expression profile of circulating microRNAs in dogs with eccentric or concentric cardiac hypertrophy. A total of 291 microRNAs in serum samples of five dogs with myxomatous mitral valve degeneration (MMVD) and five dogs with pulmonic stenosis (PS) were compared with those of five healthy dogs using microarray analysis. Results of microarray analysis revealed up-regulation of cfa-miR-130b [fold change (FC) = 2.13, p = 0.014), down-regulation of cfa-miR-375 (FC = 1.51, p = 0.014), cfa-miR-425 (FC = 2.56, p = 0.045), cfa-miR-30d (FC = 3.02, p = 0.047), cfa-miR-151 (FC = 1.89, p = 0.023), cfa-miR-19b (FC = 3.01, p = 0.008), and cfa-let-7g (FC = 2.53, p = 0.015) in MMVD group which showed eccentric cardiac hypertrophy, up-regulation of cfa-miR-346 (FC = 2.74, p = 0.032), down-regulation of cfa-miR-505 (FC = 1.56, p = 0.016) in PS group which showed concentric cardiac hypertrophy, and down-regulation of cfa-miR-30c (FC = 3.45, p = 0.013 in MMVD group; FC = 3.31, p = 0.014 in PS group) and cfa-let-7b (FC = 11.42, p = 0.049 in MMVD group; FC = 5.88, p = 0.01 in PS group) in both MMVD and PS groups. In addition, the unsupervised hierarchical clustering of differentially expressed microRNAs in each group resulted in complete separation of healthy dogs from dogs with heart diseases. Therefore, eleven microRNAs among 291 microRNAs were identified as differentially expressed circulating microRNAs related to MMVD or PS in dogs. This pilot study demonstrates that the microRNAs identified in this study could be possible candidates for novel biomarker or therapeutic target related to cardiac hypertrophy in dogs.